2017
DOI: 10.4103/0019-5413.205674
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of intramedullary interlocking nailing and minimally invasive plate osteosynthesis in extra articular distal tibial fractures

Abstract: Background:Extraarticular distal tibial fractures are among the most challenging fractures encountered by an orthopedician for treatment because of its subcutaneous location, poor blood supply and decreased muscular cover anteriorly, complications such as delayed union, nonunion, wound infection, and wound dehiscence are often seen as a great challenge to the surgeon. Minimally invasive plate osteosynthesis (MIPO) and intramedullary interlocking nail (IMLN) are two well-accepted and effective methods, but each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 25 publications
(36 reference statements)
1
24
0
Order By: Relevance
“…However, Vallier et al reported that there was no significant difference between IMN and locking plates in terms of nonunion rate, and IMN had a high rate of malalignment [35]. Other studies found similar effects between IMN and plates [29,37]. Our results are consistent with these.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, Vallier et al reported that there was no significant difference between IMN and locking plates in terms of nonunion rate, and IMN had a high rate of malalignment [35]. Other studies found similar effects between IMN and plates [29,37]. Our results are consistent with these.…”
Section: Discussionsupporting
confidence: 91%
“…The SUCRA probabilities were 55.1% for ORIF, 43.2% for IMN, and 51.7% for MIPPO (Figure 7A). Delayed union was reported in 7 trials [12,29,3133,35,37]. No significant differences were found in the incidences of delayed union of IMN, ORIF, and MIPPO (ORIF: RR=1.34; 95% CI, 0.4–3.87; P=0.594; MIPPO: RR=0.72; 95% CI, 0.35–1.72; P=0.377; Figure 6B).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Six studies were conducted in India [9, 10, 18–20], three in China [23, 26, 28], one in the UK [21], and one in Turkey [25] and the USA [24]. Nine studies [9, 10, 18–21, 25, 27] focused on closed or Gustilo patients and most of the studies [10, 1921, 2327] followed up participants for more than 12 months. Most of the studies reported the time to reunion of the tibia, except three studies [9, 10, 21].…”
Section: Resultsmentioning
confidence: 99%